An Ultramicroporous Metal–Organic Framework for Sieving Separation of Carbon Dioxide from Methane. Issue 3 (23rd September 2020) - Lin, Rui-Biao; Li, Libo; Alsalme, Ali; Chen, Banglin
Abstract : Metal–organic frameworks (MOFs) can be rationally constructed with optimal pore structure for highly selective gas separation, but developing efficient adsorbents to fulfill high sieving separation for important processes remains a challenge. Herein, an ultramicroporous MOF [Ca(C4 O4 )(H2 O)] possessing rigid 1D pore channels is applied for high sieving separation of carbon dioxide over methane. This MOF, synthesized from calcium nitrate and squaric acid, contains well‐constrained squarate linkers declining rotations or distortions of organic moieties that could enlarge the pores. These highly rigid pore apertures show sieving size for carbon dioxide capture, but, owing to their size, shape, and rigidity, act as nanosieves to block the diffusion of methane. This material shows large CO2 uptake capacity of 3.0 mmol g −1 that is higher than some MOF sieves for CO2, with negligible coadsorption of CH4 . The sieving effect of this adsorbent for CO2 /CH4 mixture is validated by breakthrough experiments under ambient conditions, showing a productivity of 3012 mmol L −1 for captured CO2 . Molecular modeling studies reveal the well accommodations of CO2 molecules in the pore channels of this MOF, facilitating to realize high sieving separation of carbon dioxide from methane. Abstract : An ultramicroporous metal–organic framework calcium squarate with optimal pore size and high pore rigidity is realized to exhibit high carbon dioxide uptake capacity but no methane adsorption, resulting in high capture productivity for carbon dioxide/methane separation at ambient conditions.